Teacher Education in the 21st Century Emerging Skills for a Changing World - Jose Hernández-Serrano, Maria (IntechOpen, 2021)
In the face of unprecedented disruption from the COVID-19 pandemic and the rapid acceleration of digital technologies, it is necessary to rethink the competences required by teachers for meeting new and flexible learning demands. Teacher training is an area constantly evolving along with emerging social challenges that are transforming educational institutions and agents. This book provides teachers with skills, innovative solutions, cutting-edge studies, and methodologies to meet education and training system demands. In our changing world, preparing teachers worldwide for the challenges and shifts of this era involves the opportunity to exchange theories, practices, and experiences such as those contained in this book.